From Grassroots to Global Governance: Ecofeminist Strategies Advancing Women’s Empowerment and Sustainable Development - Nurkhalis, Nurkhalis; Susanti, Emy; Sutinah, Sutinah (Journal Public Policy, 2026)
This study aims to examine how ecofeminist strategies contribute to advancing women’s empowerment and environmental sustainability across diverse socio-political contexts. Using a Systematic Literature Review (SLR), this study analyzes twenty-eight empirical and conceptual articles published between 2015 and 2025, sourced from Scopus and ProQuest. The review follows the PRISMA protocol, with study quality assessed using the JBI Critical Appraisal Checklist, and employs thematic analysis to identify recurring patterns and contextual determinants. The findings reveal six interconnected strategies: gender-based policy reform, economic empowerment, ecofeminist education, grassroots activism, recognition of local knowledge, and intersectional approaches. These strategies operate synergistically across political, economic, and epistemic dimensions, demonstrating that empowerment emerges from dynamic interactions among structural, cultural, and ecological factors. Key success factors include alignment with local values, multi-level collaboration, and sustained political commitment, while major barriers involve entrenched patriarchy, neoliberal co-optation, and epistemic marginalization. This study concludes that ecofeminism offers a multidimensional and context-sensitive framework that links gender justice with environmental governance. Integrating these strategies into global agendas, such as the Sustainable Development Goals and UNFCCC Gender Action Plan, can strengthen inclusive, participatory, and resilient pathways toward sustainable development.